Aspek Religi dan Kepribadian dalam Novel Tuhan, Aku Kembali Karya Haidar Musyafa - Sri Mulyani Rusli (Jurnal Ilmiah Langue and Parole, 2020)
This research is motivated by aspects of Islamic religious values with the personality contained in the novel by Haidar Musyafa, namely God I Return. The value aspects reviewed include the values of aqidah, sharia values and moral and personality values. This research aims to describe the values of aqidah, sharia and morals as well as the personalities of the characters in the Haidar Musyafa novel. This study uses a qualitative type with descriptive analysis method. Analysis of the data taken is based on religious and psychological data so that it can be concluded that the value of aqidah in the Haidar Musyafa novel includes (a) having faith in Allah SWT which is seen in Umi's character who is flat in his statement that Allah's pleasure depends on the pleasure of parents. (b) having faith in the book of Allah SWT which can be seen in the character of Jefrrey who always reads the Koran in every step. (c) have faith on the Day of Judgment which is seen when Uje dreams of death and repents. The value of sharia is reflected in the character of Apih who always reminds her children to always pray in congregation and not to leave prayers. The moral values contained in the novel include (a) morals towards the creator, namely Allah SWT, which is reflected in the character of Jefrrey who initially behaved badly then repented to become a good person. (b) morals towards fellow human beings which is reflected in the character of Jefrrey who likes to do bad things, behaves rudely and is disobedient to his parents. Who finally got the guidance to be a good person. (c) Moral towards oneself is reflected in the character of Uje who realizes his mistakes and does not torture himself any longer from disobedience. The personality aspect is reflected in the behavior of Uje who really does Allah's orders after receiving guidance, And habits that often give charity.